(untitled) (Baghdad Science Journal, 2004)
Some esters were prepared from reaction of different molecular weight of PVA with some acid chloride (prepared by reaction of acid with thionyl chloride or phosphorous pentachloride)in the presence of pyridine. The thermal and reological properties were studied. The increasing Of bulky groups decreasing stability of the thermal and reological properties.